International Newspaper Coverage of the 2013 EuroBasket for Men. (August 2017) - Ličen, Simon; Lončar, Mateja; Delorme, Nicolas; Horky, Thomas; Jakubowska, Honorata
This study examines international newspaper coverage of the 2013 European Basketball Championship for men. Generalist broadsheet newspapers in 13 countries on five continents were examined over the course of 1 year (from August 2012 until September 2013) to understand the amount and content of coverage dedicated to this major event. Results show that the host country, Slovenia, dedicated the most extensive coverage to the EuroBasket, followed by Croatia, a neighboring country. Media interest in other countries was very limited and focused almost exclusively on competitive aspects of the tournament (as opposed to organizational, tourist, or cultural angles). Of the newspapers examined, only five covered the event in the months leading up to it and only four reported the final outcome of the tournament. Generalist broadsheets thus displayed limited interest in the competition, contradicting organizers' assertions and popular belief of widespread promotional and economic benefits deriving from the event. Newspapers from countries that fielded teams at the event overwhelmingly focused on their performances. As setters of the public agenda, mainstream broadsheets exhibit very limited interest in the myriad major sports events organized worldwide. Hosting such events are not by default the promotional and economic boon organizers argue and the public believes.